Lumbosacral Soft Tissue Mass in a Newborn: A Clinical Case with a Difficult Diagnosis - Ceratto, Simone; Basso, Maria Eleonora; Savino, Francesco (Frontiers in Pediatrics, 2017)
Many types of dorsal neoplasm of early infancy are described in literature ranging from benign to aggressive. Some are more common while others quite unusual. Here we describe a newborn with a lumbosacral soft tissue mass. Positivity of S-100 and Vimentin was compatible with the neural cell line and the high proliferation rate of major activity cells (biopsy Ki67 20%) suggests an aggressive nature. An exclusively surgical approach was chosen and no clinical or radiological signs of recurrence have been observed after two years of follow-up. This case is atypical for location, histological pattern, radiological aspect and clinical behavior. Diagnosis is hard to define and limited to a mesenchymal neoplasia with myxoid tracts. The described aspects raise concerns about clinical and therapeutic approach, classification and radiological follow-up of sacral tissue masses in newborns.